THE IRRATIONALITY OF CONSUMERS CHOOSING PLANE TICKETS: CASE STUDY OF GENERATION Z REPRESENTATIVES IN THE CZECH REPUBLIC (Perner's Contacts, 2020)
Economic models can be used to describe consumer behavior or to predict expected behavior of the consumers. In order for the application of the selected economic model to describe realistically the issue under study, it is necessary that the individual components of the economic model are able to reliably identify and possibly even quantify main characteristics of the studied problematique. In the last few years, one of the basic theses based on which several economic models are built upon has been "questioned" within the scientific community, namely the one that portraits human as always rationally behaving individual. The goal of this article is to verify whether, in the framework of predicting consumer behavior, one can still use a person as a so-called homo oeconomicus (economic man who always behaves rationally) or whether this theory has been already overcome, and human behavior should be rather described as irrational. To validate the theory of irrationality in the context of consumer behavior, an experiment in the field of air transport will be used, monitoring consumer decision making while choosing the plane tickets.